An Interprofessional Simulation-Based Learning Activity for Nursing and Physiotherapy Students - Dennis, Diane; Furness, Anne; Duggan, Ravani; Critchett, Siana (2017)
© 2017 International Nursing Association for Clinical Simulation and Learning Background The ability to work interprofessionally is considered a core competency for healthcare graduates because it promotes collaborative patient-centred clinical practice. Methods This mixed methods observational study utilised simulation of a patient-centred scenario to deliver an interprofessional learning activity to both nursing and physiotherapy students. Results Over one day during 2015, 198 students undertook the activity, with all completing two surveys evaluating the experience. Results suggested that they both enjoyed and valued the experience, especially in relation to the clinical interaction and learning that took place and the opportunity the scenario provided them to work as a team member. Conclusions Future interprofessional simulation activities will be able to utilise the generic self and peer-assessment framework and timetabling resources developed.